Clinical experience with 0.01% atropine for myopia control in children in Azerbaijan - Galbinur, A P (Vestnik oftal'mologii, 2025)
This study evaluated changes in ocular parameters in patients with progressive myopia receiving 0.01% atropine. The study included 35 children (18 girls, 51.4%; and 17 boys, 48.6%) aged 4-15 years. Among them, 20 (57.2%) had one myopic parent and 2 (5.7%) had both parents with myopia. The study consisted of four stages: stage 1 - initial examination; stage 2 - follow-up after 8 months without treatment; stage 3 - follow-up after 12 months of treatment; stage 4 - follow-up 6 months after treatment cessation. Atropine 0.01% was instilled daily at bedtime in four courses of 1.5 months each, totaling 12 months of follow-up. All patients had an astigmatic component. At stage 2, nearly all children showed progression of myopia, with a statistically significant increase in spherical equivalent in 63 (90%) eyes by an average of 0.70 D ( =0.000; <0.001). A similar trend was observed in axial length, which increased by 0.35±0.09 mm ( =0.000; <0.001). At stage 3, stabilization was observed in both spherical equivalent and axial length. The mean difference in spherical equivalent between stages 2 and 3 was minor (-0.08 D) and not statistically significant ( =0.127; <0.050). Stabilization was also noted for axial length, with a change of 0.04 mm ( =0.034; <0.050). Differences between stages 3 and 4 in spherical equivalent were minimal and statistically insignificant (-0.01 D; =0.012). The use of 0.01% atropine over one year in four 1.5-month courses stabilizes the progression of myopia in children. This method is an effective and acceptable option for controlling myopia in preschool and school-aged children.